The Influence of Work life balance on Employee engagement among workers in Pampanga. Philippines: A Structural Equation Modelling Approach - Dayrit, Joycelyn S. (International Journal of Psychosocial Rehabilitation, 2020)
The study examines the influence of work life balance on employee engagement. The participants of the study are employees of Pampanga Chamber of Commerce(PAMCHAM) member organizations in the following sectors: banking, education and auto sales sector. A stratified sampling was used in identifying samples. Moreover, a convenience sampling technique was also employed. The partial least squares – structural equation modeling (PLS-SEM) using WarpPLS 6.0 software was employed to estimate the parameters of the structural model. Analysis of the data revealed that family-work conflict is significantly and negatively related to employee engagement. With regards to the relationship between work-life conflict and employee engagement, the results showed that the relationship is negative but insignificant. In terms of the relationship between family satisfaction and employee engagement, the findings revealed that the two (2) constructs are significantly and positively related. Lastly, the relationship between work satisfaction and employee engagement were found to be significantly and positively related.